New Ecological Role of Seaweed Secondary Metabolites as Autotoxic and Allelopathic - Sudatti, Daniela Bueno; Duarte, Heitor Monteiro; Soares, Angélica Ribeiro; Salgado, Leonardo Tavares; Pereira, Renato Crespo (Frontiers in Plant Science, 2020)
Allelopathy and autotoxicity are well-known biological processes in Angiosperms, but are very little explored or even unknown in seaweeds. In this study, extract and major pure compounds from two distinct populations of the red seaweed Laurencia dendroidea were investigated to evaluate the effect of autotoxicity through auto- and crossed experiments under laboratory conditions, using chlorophyll fluorescence imaging to measure inhibition of photosynthesis (ΦPSII) as variable response. Individuals of L. dendroidea from Azeda beach were inhibited by their own extract (IC50= 219 µg/ml) and major compound elatol (IC50= 87 µg/ml; both chemicals also inhibited this seaweed species from Forno beach (IC50= 194 µg/ml for extract and IC50= 277 µg/ml for elatol). By contrast, extract of L. dendroidea from Forno and its major compound obtusol showed no inhibitory effect in individuals of both populations; but obtusol was insoluble to be tested at higher concentration, which could be active as observed for elatol. Azeda population displayed higher susceptibility to Azeda extract and to elatol, manifested on the first day, unlike Forno individuals, in which the effect was only detected on the second day; and inhibition of ΦPSII was more pronounced at apical than at basal portions of the thalli of L. dendroidea. This first finding of seaweed autotoxicity and allelopathic effects revealed the potential of the chemistry of secondary metabolites for intra- and inter-populational interactions, and for structuring seaweed populations.